The Nature of Recognition in TEFL Teachers’ Lives - Barbara Scholes Gillings de González (Profile: Issues in Teachers' Professional Development)
This article aims at sharing a vital issue that emerged from the findings of a qualitative research study into collective responses of teachers of English as a foreign language to an extended change process in their Mexican university context from 1989 to 2003. The data generation process employed was comprised of semi-structured interviews as well as the concurrent analysis of the data, based on aspects of grounded theory. The results of this inquiry demonstrated features of the complexity paradigm of educational change. In particular, how teachers' receptivity to change was strongly influenced by the teachers' transforming construal of their professional identities owing to the growing recognition they acquired in their context.